DINÂMICA DISCURSIVA E O ENSINO DE FÍSICA: ANÁLISE DE UM EPISÓDIO DE ENSINO ENVOLVENDO O USO DE UM TEXTO ALTERNATIVO - Alice Assis; Odete Pacubi Baierl Teixeira (Ensaio Pesquisa em Educação em Ciências, 2007)
This paper focuses the discursive dynamic analysis among pupils and teacher using an alternative text called "Our Universe", in physics classes for young and adult people. A teaching episode about physics concepts discussion was used and the results showed that this text was potentially significant to pupils, who had their curiosity and interest increased, besides of their relating of discussed topics with previous knowledge. This fact associated to the teacher's interceding role, who assumed a dialogical approach, resulted in an easier students' significant critical leaning.